Feeding and feedback in nuclei of galaxies. Issue Volume 15:Issue S359(2020) (March 2019) - Audibert, Anelise; Combes, Françoise; García-Burillo, Santiago; Dasyra, Kalliopi
Abstract: Our aim is to explore the close environment of Active Galactic Nuclei (AGN) and its connection to the host galaxy through the morphology and dynamics of the cold gas inside the central kpc in nearby AGN. We report Atacama Large Millimeter/submillimeter Array (ALMA) observations of AGN feeding and feedback caught in action in NGC613 and NGC1808 at high resolution (few pc), part of the NUclei of GAlaxies (NUGA) project. We detected trailing spirals inside the central 100 pc, efficiently driving the molecular gas into the SMBH, and molecular outflows driven by the AGN. We present preliminary results of the impact of massive winds induced by radio jets on galaxy evolution, based on observations of radio galaxies from the ALMA Radio-source Catalogue.